Antioxidant and Cytotoxic Activities of Postpartum Herbal Remedies Use in Aceh, Indonesia - Saudah Saudah; Rubiah Rubiah; Zumaidar Zumaidar; Itsnatani Salma; Rahmawati Rahmawati (Malacca Pharmaceutics, 2026)
Traditional medicinal plants continue to play an important role in postpartum care in Aceh, Indonesia, yet their pharmacological properties remain insufficiently documented. This study examined the phytochemical composition, antioxidant capacity, and cytotoxic profile of five commonly used postpartum plants: Glochidion zeylanicum var. zeylanicum, Glochidion obscurum, Mesua ferrea, Vitex pinnata, and Salix babylonica. Ethanolic leaf extracts were prepared by macerating the leaves and analyzed for major secondary metabolites. Antioxidant activity was evaluated using the DPPH radical scavenging assay, while cytotoxicity was assessed through the brine shrimp lethality test (BSLT). All extracts contained flavonoids, phenolics, tannins, and terpenoids, with alkaloids detected in most species. G. obscurum showed the strongest antioxidant activity (IC50 = 2.30 µg/mL), followed by M. ferrea, V. pinnata, and G. zeylanicum, whereas S. babylonica exhibited moderate activity. BSLT results indicated high cytotoxicity in M. ferrea, V. pinnata, and S. babylonica (LC50 < 10 µg/mL), while G. obscurum and G. zeylanicum demonstrated moderate toxicity. These findings provide scientific support for the traditional postpartum use of these plants, particularly regarding antioxidant and restorative functions. However, the strong cytotoxicity observed in several species highlights the need for cautious dosage and further toxicological validation. Additional studies are recommended to isolate active constituents and clarify their safety and therapeutic relevance.